39.8k views
3 votes
Question 3. Let f:X --> Y be a function. (a) Recall that for C CY, the inverse image of C is the set f-1(C) = x E X. Let A, B CY. Prove that f-1(ANB) Cf-1(A) n f-1(B). (b) Recall that for D C X, the image of D under f is the set f(D) = {f(x) E YX E X}. Let A, B C X. Prove that f(An B) c f(A)n F(B). Find an example of a function f and sets A and B such that f(ANB) = Ø but f(A) n f(B) + Ø.

User Jeff Stock
by
4.9k points

1 Answer

4 votes

Answer:

Explanation:

a) We want to prove that
f^(-1)(A\cap B)\subset f^(-1)(A)\cap f^(-1)(B). Then, we can do that proving that every element of
f^(-1)(A\cap B) is an element of
f^(-1)(A)\cap f^(-1)(B) too.

Then, suppose that
x\in f^(-1)(A\cap B). From the definition of inverse image we know that
f(x)\in A\cap B, which is equivalent to
f(x)\in A and
f(x)\in B. But, as
f(x) \in A we can affirm that
x\in f^(-1)(A) and, because
f(x)\in B we have
x\in f^(-1)(B).

Therefore,
x\inf^(-1)(A)\cap f^(-1)(B).

b) We want to prove that
f(A\cap B) \subset f(A)\cap f(B). Here we will follow the same strategy of the above exercise.

Assume that
y\in f(A\cap B). Then, there exists
x\in A\cap B such that
y=f(x). But, as
x\in A\cap B we know that
x\in A and
x\in B. From this, we deduce
f(x)=y\in f(A) and
f(x)=y\in f(B). Therefore,
y\in f(A)\cap f(B).

c) Consider the constant function
f(x)=1 for every real number
x. Take the sets
A=(0,1) and
B=(1,2).

Notice that
A\cap B = (0,1)\cap (1,2)=Ø, so
f(A\cap B)=Ø. But
f(A) = \{1\} and
f(B) = \{1\}, so
f(A)\cap f(B) =\{1\}.

User Rollen
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.